PENGARUH KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI DAN KEPUASAN KERJA PEGAWAI BAKTI PADA SEKRETARIAT DPRK LHOKSEUMAWE - Yusrizal Yusrizal; A. Hadi Arifin; Naufal Bachri (Universitas Malikussaleh, 2020)
This study aims to observe the influnce of communication and leadership style to motivation and job satisfaction of employee salaries on Lhokseumawe secretariat the council representative people. This research is a quantitative research described by description. The instrument of data collection is a questioner. The sample of this research is 123 employee salaries on Lhokseumawe secretariat the council representative people. Data analysis method used is AMOS-22 program with SEM and Sobel test model. The result of data analysis get some findings as follows those are communication has a positive and significant effect to motivation, leadership style has a positive and significant effect to motivation, communication has a positive and significant effect to job satisfaction, leadership style has a positive and significant effect to job satisfaction, motivation has a positive and significant effect to job satisfaction, motivation mediates fully the influence between communication to job satisfaction, motivation mediates partially the influence between leadership style to job satisfaction. Keywords: Communication, Leadership Style, Motivation, Job Satisfaction